A Study of Reliability of Multi‐State Systems with Two Performance Sharing Groups. (19th February 2016) - Peng, Rui; Liu, Hanlin; Xie, Min
Abstract : The performance sharing can be widely seen in different kinds of engineering systems, such as meshed power distribution systems and interconnected data transmission systems. This paper presents a study of systems consisting of multi‐state units connected as two performance sharing groups, and the suggested methodology can be adapted for the case of three or more performance sharing groups. To be more general, the system unit is allowed to be in one single performance sharing group or both. Each unit has a random demand to satisfy, and the units can transmit capacity with each other given that the total performance transmitted in each performance sharing group does not surpass its maximum transmission capacity. An algorithm based on the universal generating function technique is proposed to evaluate the system reliability and the expected system performance deficiency. Copyright © 2016 John Wiley & Sons, Ltd.